Exploring the Cognitive Effects of Closed‐Serial and Closed‐Continuous Exercise in Aging: A Study on Dance and Endurance Training. - Forte, R.; Caputo, O.; Vecchiato, C.; Sarto, F.; Martino, G.; Tedesco, G.; Marino, M.; Angrilli, A.; De Vito, G.; Narici, M. (European Journal of Sport Science, 2026)
Physical exercise benefits both cognition and physical health in aging, but it remains unclear whether benefits derive mainly from intensity or task complexity. Continuous exercises involve repetitive and predictable movements (e.g., running), whereas serial exercises (e.g., dancing) integrate varied motor sequences, and are cognitively more demanding. Clarifying the contribution of intensity and complexity is crucial for designing physically safe yet cognitively stimulating programs, maximizing preventive and rehabilitative potential in older adults. The aim of the study was to compare the ability of continuous versus serial exercises to improve executive functions. Seventy‐two participants (mean age 66.8) were assigned to three groups: dance (DNC), endurance (END), and inactive controls (INA). Executive functions were assessed through the Flanker, Corsi‐Block, and Trail Making tests. Groups were compared with MANOVA, followed by ANOVAs and LSD post‐hoc. A group effect emerged in the Flanker task (p = 0.006). END showed faster overall response times (RT) than DNC (p = 0.002) and INA (p < 0.001); DNC and INA did not differ. Incongruent RT tended to be faster in END versus DNC (p = 0.068) and was faster versus IAC (p = 0.003). For congruent RT, DNC and END outperformed IAC (p = 0.002; p = 0.001). Conflict cost was lower in DNC versus INA (p = 0.041) and END (p = 0.043), with no INA versus END difference. Continuous exercise enhanced general processing speed, whereas serial exercise appeared more effective for cognitive flexibility and selective attention. These findings support prior evidence to guide future large‐scale interventions aimed at optimizing exercise‐based cognitive training for older adults. Highlights: Continuous exercise enhances processing speed in aging.Dance supports flexibility and selective attention.Exercise complexity shapes cognitive outcomes beyond intensity.Different exercise modes target distinct executive processes.